Extracorporeal shock wave therapy in situ — novel approach to obtain an activated fat graft. (20th October 2017) - Priglinger, E.; Sandhofer, M.; Peterbauer, A.; Wurzer, C.; Steffenhagen, C.; Maier, J.; Holnthoner, W.; Nuernberger, S.; Redl, H.; Wolbank, S.
Abstract: One of the mainstays of facial rejuvenation strategies is volume restoration, which can be achieved by autologous fat grafting. In our novel approach, we treated the adipose tissue harvest site with extracorporeal shock wave therapy (ESWT) in order to improve the quality of the regenerative cells in situ . The latter was demonstrated by characterizing the cells of the stromal vascular fraction (SVF) in the harvested liposuction material regarding cell yield, adenosine triphosphate (ATP) content, proliferative capacity, surface marker profile, differentiation potential and secretory protein profile. Although the SVF cell yield was only slightly enhanced, viability and ATP concentration of freshly isolated cells as well as proliferation doublings after 3 weeks in culture were significantly increased in the ESWT compared with the untreated group. Likewise, cells expressing mesenchymal and endothelial/pericytic markers were significantly elevated concomitant with an improved differentiation capacity towards the adipogenic lineage and enhancement in specific angiogenic proteins. Hence, in situ ESWT might be applied in the future to promote cell fitness, adipogenesis and angiogenesis within the fat graft for successful facial rejuvenation strategies with potential long‐term graft survival.